Primary structure of superoxide dismutase from Pseudoalteromonas haloplanktis by a combination of automatic Edman degradation and ESI/Q-TOF mass spectrometry - DI MARO A; CHAMBERY A; CASTELLANO, IMMACOLATA; RUOCCO, MARIA ROSARIA; MASULLO M; DE VENDITTIS, EMMANUELE; PARENTE A. (country:ITA, 2005)
Superoxide dismutase (SOD) is a metalloenzyme that has a protective effect against toxic superoxide radicals in both aerobic and anaerobic organisms. SODs have been classified into two families on the basis of their different structural folding and metal content (Cu/Zn in one family and Fe or Mn in the other one). SODs isolated from extremophilic organisms are suitable models to study the structure-function relationships and the molecular and evolutive mechanisms for the adaptation of proteins to extreme environments. We have previously isolated a SOD from the psychrophilic eubacterium Pseudoalteromonas haloplanktis (PhSOD), isolated from Antarctic marine sediments and adapted to grow at low temperatures. This enzyme has a specific activity of 6500 U/mg and according to preliminary characterization, PhSOD could be classified as a Fe-SOD. In this communication the rapid characterization of primary structure of PhSOD was determined using a combined approach based on automatic Edman degradatiion and electrospray ionization mass spectrometry (ESI-MS/MS). The information gathered by this approach combined with automated recording and interpretatiion of data enabled full primary structure determination of SOD with minimal time and material consumption (200 ug/10 nmoles). The primary structure of PhSOD was obtained using the following experimental steps: i) verification of the protein purity and identity by SDS-PAGE and ESI-MS; ii) enzymatic cleavage by endoproteinase Asp-N; iii) sequence determination of Asp-N peptides by Edmann degradation and iv) overlapping with tryptic peptides analysed by Q-Tof mass spectrometry and by homology with reference proteins. ESI-MS analysis of native PhSOD, obtained from RP-HPLC as the last purification step, showed that its molecular mass was 21328.50 +/- 0.40. Automated Edman degradation of peptides obtained from endoproteinase Asp-N and separated by RP-HPLC, provided most of the amino acid sequence of PhSOD. However, with this first set of data, various amino acid residues were not ...